Virtual environment for education and training - Low, Yoke Hwee. (2008)
This dissertation begins with a review on case studies using VR technology in industrial, medical, education and military training followed by an analysis on how VR can be used to resolve the various problems encountered in the current educational establishment. It is then followed by a section discussing the benefits and problem VR faced. Next, different network infrastructures will be discussed on how they can be employed in a multi-user virtual environment.